A spiral passive electromagnetic sensor (SPES) for wireless and wired structural health monitoring. (7th March 2016) - Iervolino, Onorio; Meo, Michele
Abstract: A major goal of structural health monitoring (SHM) in the past decade has been to improve crack detection and monitoring while reducing maintenance and installation costs. This would normally require placing many sensors over a large area, powering and interrogating them. On the other hand, operational aspects such as the temperature effects, battery life, and weight penalties have fundamental roles in the sensor design. In addition, small dimension of the sensors, low cost, and non-contact measurement system for data retrieval are very often required. We present a non-destructive evaluation/structural health monitoring (NDE/SHM) sensor that can be remotely interrogated without any wiring for data transmission or power supply. A spiral passive electromagnetic sensor (SPES) was designed and fabricated. The sensor is a planar 2D inductor circuit of scalable size that resonates at a characteristic frequency when exposed to an electromagnetic field. The specific frequency is dependent on the inductance of the inductor, its parasitic capacitance and resistance, and the electrical properties of the surrounding area. A change in a material's permittivity or permeability due to damage can be sensed through the SPES device. The sensor was tested by using a passive wireless resonant telemetry scheme and a wired interrogation method. Both conductive (i.e. carbon fiber) and non-conductive (i.e. fiber glass) structures were monitored showing very promising capabilities and accuracy in detecting defects/damage in composite structures. The use of the proposed sensor eliminates the need for on-board power and exposed interconnects, reduces the instrumentation mass and volume, increases the reliability due to the continuous operation even in case of a damaged sensor, and increases the life of the device.